The RMS TC-Rain Model - Jürgen Grieser; Steve Jewson (Meteorologische Zeitschrift, 2012)
Tropical-cyclone rain causes inland flooding, land-slides and mud-slides, and these perils are a risk for human life and property in areas prone to tropical cyclones. We describe a parameterized tropical-cyclone rain model which is simple enough to be run several hundred thousand times and hence can be used to estimate these risks. The model is based on climatological off-shore rain rates parameterized by R-CLIPER, but with a number of important improvements: the model takes into account rain enhancement due to orography and landfall; rain rates are spatially distributed to match the asymmetry of observed tropical cyclone rain, including rain bands and the effects of extratropical transition, and rain drift is parameterized as a function of wind speed. The model is calibrated with respect to observations of 358 US-landfalling tropical cyclones during the period 1948 to 2007. Although not designed for forecasting the model is then used to forecast the rainfall for six US-landfalling tropical cyclones in 2008 (the most recent active season) as an independent test. A statistical track set consisting of tracks of North-Atlantic tropical cyclones covering 100,000 years is used in order to estimate maps of return levels of tropical cyclone rain for the US mainland.